Anthropogenic Control Over Wintertime Oxidation of Atmospheric Pollutants. Issue 24 (20th December 2019) - Haskins, J.D.; Lopez‐Hilfiker, F. D.; Lee, B. H.; Shah, V.; Wolfe, G. M.; DiGangi, J.; Fibiger, D.; McDuffie, E. E.; Veres, P.; Schroder, J. C.; Campuzano‐Jost, P.; Day, D. A.; et al.
Abstract: During winter in the midlatitudes, photochemical oxidation is significantly slower than in summer and the main radical oxidants driving formation of secondary pollutants, such as fine particulate matter and ozone, remain uncertain, owing to a lack of observations in this season. Using airborne observations, we quantify the contribution of various oxidants on a regional basis during winter, enabling improved chemical descriptions of wintertime air pollution transformations. We show that 25–60% of NOx is converted to N2 O5 via multiphase reactions between gas‐phase nitrogen oxide reservoirs and aerosol particles, with ~93% reacting in the marine boundary layer to form >2.5 ppbv ClNO2 . This results in >70% of the oxidizing capacity of polluted air during winter being controlled by multiphase reactions and emissions of volatile organic compounds, such as HCHO, rather than reaction with OH. These findings highlight the control local anthropogenic emissions have on the oxidizing capacity of the polluted wintertime atmosphere. Plain Language Summary: During summer, rapid transformations of primary pollutants, those emitted directly into the atmosphere, into secondary pollutants, such as particulate matter and ozone, are driven by reactions with the hydroxyl radical, formed in the atmosphere when sunlight strikes ozone in the presence of water vapor. During winter, when there is less sunlight and water vapor, production of this radical is lower. Yet the conversion of primary pollutants into secondary pollutants still occurs rapidly, pointing to a misunderstanding in the chemical processes that drive this conversion during winter. Using aircraft data collected across the northeast United States during the winter of 2015, we show that reactions with radicals arising from atypical precursors, such as nitryl chloride, account for more than 70% of the reactions that directly emitted pollutants undergo. We show that during winter, the formation of these radicals is tied to human activities. Our data provide critical constraints for improving the descriptions of chemical processes in air quality models, which will help guide improved air quality policy. Other regions of the world, such as China, Europe, and northern India, also experience this seasonal chemical shift in the atmosphere. Our findings, therefore, have global scale implications for understanding wintertime pollution transformations and transport. Key Points: Observations show atypical radical precursors drive >70% of atmospheric oxidation in polluted air over the northeast United States during winter Anthropogenic emissions and multiphase chemistry largely control the abundance of these atypical radical precursors Improved descriptions of these radical sources in air quality models are needed to predict future trajectories in wintertime air pollution